Sodium-Glucose Co-Transporter 2 Inhibitors May Change the Development of Urinary Tract and Hematological Malignancies as Compared With Dipeptidyl Peptidase-4 Inhibitors: Data of the Post-Hoc Analysis of a Nationwide Study - Rokszin, György; Kiss, Zoltán; Sütő, Gábor; Kempler, Péter; Jermendy, György; Fábián, Ibolya; Szekanecz, Zoltán; Poór, Gyula; Wittmann, István; Molnár, Gergő Attila (Frontiers in Oncology, 2021)
Background: In diabetes mellitus, during the last years, cancer became of equivalent importance as a cardiovascular disease in terms of mortality. In an earlier study, we have analyzed data of the National Health Insurance Fund (NHIF) of Hungary with regards of all patients treated with SGLT2 inhibitors (SGLT2i) vs. those treated with DPP-4 inhibitors (DPP4i) in a given timeframe. In propensity score matched groups of SGLT2i vs. DPP-4i treated patients, we found a lower incidence of cancer in general. In this post-hoc analysis we aimed to obtain data on the incidence of site-specific cancer incidence. Patients and methods: All patients starting an SGLT2i or a DPP-4i between 2014 and -2017 in Hungary were included; the two groups (SGLT2i vs. DPP-4i) were matched for 54 clinical and demographical parameters. The follow-up period was 639 vs. 696 days, respectively. Patients with a letter ‘C’ ICD-10 code have been chosen, and those with a known malignancy within a year before study the onset of the study have been excluded from the analysis. Results: We found a lower risk of urinary tract [HR 0.50 (95% CI: 0.32-0.79) p=0.0027] and hematological malignancies [HR 0.50 (95% CI: 0.28-0.88) p=0.0174] in patients treated with SGLT2i vs. those on DPP-4i. Risk of other types of cancer (including lung and larynx, lower GI tract, rectum, pancreas, non-melanoma skin cancers, breast, or prostate) did not differ significantly between the two groups. When plotting absolute risk difference against follow-up time, an early divergence of curves was found in case of prostate, urinary tract, and hematological malignancies, while whereas late divergence can be seen in case of cancers of the lung and larynx, the lower gastrointestinal tract, and the breast. Conclusions: Urinary tract and hematological malignancies were less frequent in patients treated with SGLT2i vs. DPP-4i. An early vs. late divergence could be observed for different cancer types, that which deserves requires further studies.